2018
DOI: 10.22441/mix.2018.v8i2.010
|View full text |Cite
|
Sign up to set email alerts
|

Peran Komitmen Organisasional Dalam Memediasi Pengaruh Kompetensi, Pelatihan Dan Budaya Organisasi Terhadap Kinerja Perawat

Abstract: Abstract. Research aim to analyze influence of 1) Competencies on Organtizational Commitment. 2) Training on Organtizational Commitment. 3) Organization Culture on Organtizational Commitmen. 4) Competencies on Nurses’ Performance. 5) Training on Nurses’ Performance. 6) Organization Culture on Nurses’ Performance. 7) Organizational Commitment on Nurses’ Performance. 8) Role mediation of Organizational Commitmen within the influence of Competencies on Nurses’ Performance. 9) Role mediation of Organizational Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
3
11
0
4
Order By: Relevance
“…The results of this study are in line with the results of previous studies conducted by (Rantesalu et al, 2016), (Kurniasari et al, 2018) and (Saputri & Muhsin, 2018) which states that organizational commitment plays a positive and significant role in mediating competence in employee performance. that organizational commitment is very capable of supporting the relationship of competence on employee performance, meaning that the effect of competence on employee performance is able to be conveyed properly by organizational commitment.…”
Section: The Effect Of Organizational Commitment On Employee Performasupporting
confidence: 92%
“…The results of this study are in line with the results of previous studies conducted by (Rantesalu et al, 2016), (Kurniasari et al, 2018) and (Saputri & Muhsin, 2018) which states that organizational commitment plays a positive and significant role in mediating competence in employee performance. that organizational commitment is very capable of supporting the relationship of competence on employee performance, meaning that the effect of competence on employee performance is able to be conveyed properly by organizational commitment.…”
Section: The Effect Of Organizational Commitment On Employee Performasupporting
confidence: 92%
“…The results of this study follow the results of research by Anggraini (2020), Choirunnisa & Koestiono (2022), Distyawaty (2019), Kurniasari et al (2018), Randa et al (2018), Wotulo et al (2018) who concluded that the direct contribution of competence variables to employee performance where competence is an essential supporting factor needed by an employee in working in a company, the better the competence possessed by the employee, the better the performance that the employee will produce to support activities work in the company. The results of this study are also in line with the results of Distyawaty's research (2019) Supervisory Apparatuses of the Regional Inspectorate of Central Sulawesi Province which found that it was partially proven that competence variables have a significant effect on employee performance.…”
Section: The Effect Of Competence On Employee Performancesupporting
confidence: 88%
“…The results of this study accept the hypothesis that commitment has a significant effect on competence on employee performance. The results of this study follow the results of Kurniasari et al (2018) dan Martini et al (2020) it can be concluded that competence indirectly through commitment has a positive and significant effect on performance, which means that if competence increases, then this will increase commitment which will then improve employee performance and conversely a decrease in competence will reduce commitment which will then reduce employee performance.…”
Section: The Effect Of Commitment To Mediate Competence On Employee P...supporting
confidence: 81%
“…Previous research has shown the influence of organizational culture on employee performance (Karinda, 2016;Shahzad et al, 2017;Aboramadan et al, 2019;Tan, 2019). Organizational culture turns out to have an insignificant influence on employee performance based on research conducted by Putriana et al (2015) and Kurniasari (2018).…”
Section: Empirical Studiesmentioning
confidence: 96%
“…Various research results confirm that organizational culture has a positive effect on employee performance. On the other hand, Putriana (2015) and Kurniasari (2018) prove that organizational culture has not been able to significantly improve employee performance.…”
mentioning
confidence: 99%